Mechanisms of reduced interspecific interference between territorial species. (11th October 2021) - McEachin, Shawn; Drury, Jonathan P; Anderson, Christopher N; Grether, Gregory F
Abstract: Interspecific territoriality has complex ecological and evolutionary consequences. Species that interact aggressively often exhibit spatial or temporal shifts in activity that reduce the frequency of costly encounters. We analyzed data collected over a 13-year period on 50 populations of rubyspot damselflies ( Hetaerina spp.) to examine how rates of interspecific fighting covary with fine-scale habitat partitioning and to test for agonistic character displacement in microhabitat preferences. In most sympatric species, interspecific fights occur less frequently than expected based on the species' relative densities. Incorporating measurements of spatial segregation and species discrimination into the calculation of expected frequencies accounted for most of the reduction in interspecific fighting (subtle differences in microhabitat preferences could account for the rest). In 23 of 25 sympatric population pairs, we found multivariate differences between species in territory microhabitat (perch height, stream width, current speed, and canopy cover). As predicted by the agonistic character displacement hypothesis, sympatric species that respond more aggressively to each other in direct encounters differ more in microhabitat use and have higher levels of spatial segregation. Previous work established that species with the lowest levels of interspecific fighting have diverged in territory signals and competitor recognition through agonistic character displacement. In the other species pairs, interspecific aggression appears to be maintained as an adaptive response to reproductive interference, but interspecific fighting is still costly. We now have robust evidence that evolved shifts in microhabitat preferences also reduce the frequency of interspecific fighting. Abstract : Can species with similar territorial signals avoid costly fights, and if so, how? To answer these questions, we analyzed data from over a decade of field research on 10 species of territorial damselflies. We found that fights occur between species less frequently than expected by chance, for two distinct reasons. Some species have diverged over evolutionary time in territorial signals, while others have diverged in microhabitat preferences, which reduces the frequency of costly encounters.